Implementing Technological Strategies to Improve Listening Skills for Young-Adult Students in the “Alfonso Herrera” Higher Technological Institute - Chalapú Puentestar, Daniela Paulina (2021)
To identify difficulties in listening comprehension in order to design and implement technological strategies to improve this skill during the learning process in students of A1 English level, from the “Alfonso Herrera” Higher Technological Institute, located in El Angel city, Carchi province.